2010
DOI: 10.1002/ptr.3193
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pycnogenol® on glucose transport in mature 3T3‐L1 Adipocytes

Abstract: Pycnogenol, a procyanidins-enriched extract of Pinus maritima bark, possesses antidiabetic properties, which improves the altered parameters of glucose metabolism that are associated with type 2 diabetes mellitus (T2DM). Since the insulin-stimulated antidiabetic activities of natural bioactive compounds are mediated by GLUT4 via the phosphatidylinositol-3-kinase (PI3K) and/or p38 mitogen activated protein kinase (p38-MAPK) pathway, the effects of pycnogenol were examined on the molecular mechanism of glucose u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…The studies indicate that Pyc components are highly bioavailable. Pyc is a procyanidin‐enriched extract of Pinus pinaster bark, and it consists of a variety of flavonoids, which are known as potent antioxidants (Lee et al ., ). Uniquely, Pyc displays greater biologic effects as a mixture than its purified components do individually, indicating that the components interact synergistically (Masquelier et al ., ; Packer et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…The studies indicate that Pyc components are highly bioavailable. Pyc is a procyanidin‐enriched extract of Pinus pinaster bark, and it consists of a variety of flavonoids, which are known as potent antioxidants (Lee et al ., ). Uniquely, Pyc displays greater biologic effects as a mixture than its purified components do individually, indicating that the components interact synergistically (Masquelier et al ., ; Packer et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Recent reports have indicated that gallic acid can increase GLUT4 translocation via the Akt-insulin-independent pathway, up-regulation of PPAR-␥ expression [24,26], and decreasing the oxidative stress-related diabetic complications [33]. Most previous studies on the normoglycemic effects of other natural compounds are primarily focused on the antioxidant effect [33], GLUT4 translocation [36,37], glucose uptake [24,38], Akt [37][38][39], and AMPK [40,41] regulation to enhance insulin sensitivity. Rutin, a well-known flavonoid in many food plants, enhances Akt phosphorylation and improves insulin resistance [14,15].…”
Section: Discussionmentioning
confidence: 99%
“…It is a procyanidin-enriched extract of Pinus pinaster bark consisting of a variety of flavonoids, which are known as potent antioxidants. 38 PYC ® shows various beneficial health effects against different types of diseases. 17 PYC ® has been extensively used in Europe as a dietary food supplement.…”
Section: Discussionmentioning
confidence: 99%